Elasticity and causality among electricity generation from renewable energy and its determinants in Malaysia - Bekhet H.A.; Harun N.H. (Econjournals, 2023)
Renewable energy (RE) is a significant issue in attaining low-carbon emissions for Malaysias economic development path. Therefore, this study investigates the determinants (capital, labor, economic growth, and financial development [FD]), which has an influence on RE generation, using time-series data from 1982 to 2015 period. The augmented CobbDouglas production function, F-bound test, and vector error correction model are employed to achieve the objectives of the study. The result of the analysis indicates a dynamic relationship among these variables. The long-run elasticity of capital and labor promotes RE generation, while the responsiveness of economic growth and FD undermine electricity generation from RE. Furthermore, there is long-run bidirectional causal relationship between capital and RE generation. Similarly, the feedback effect is found between labor and electricity generation from RE. Economic growth and FD are found to influence RE generation. Accordingly, the Malaysian government should pursue policies to enhance the utilization of RE sources toward national electricity supply security and sustainable socio-economic development. 2017, Econjournals. All rights reserved.